Remarks on the reasoning: The morals of a Hungarian expulsion decision in times of pandemic - Csatlós, Erzsébet (Central European Public Administration Review, 2021)
Several Iranian university students were expelled from Hungary to Iran due to their (allegedly) unlawful behaviour during their quarantine period at the outburst of the Covid-19 pandemic on grounds of being a threat to public policy and public security. The case reveals a worrisome practice in the reasoning of expulsion decisions, irrespective of the pandemic. By analysing a judgment on the review of an administrative decision on expulsion, the article explores the normative circumstances of the legal institutions appearing in the case. By comparing international, European Union, and Hungarian constitutional practice, the study reveals a controversial legal practice. It not only evaluates the case, but draws attention to the role, quality, and legal significance of reasoning of administrative acts which lately, with a quickly changing legislation, seems to be forgotten.
Keywords: effective legal remedy; expulsion; fair procedure; izgon; obrazložitev odločb; pošten postopek; procedural guarantees; procesna jamstva; reasoning of decisions; učinkovita pravna sredstva